A place to grow older … alone? Living and ageing as a single older lifestyle migrant in the Azores - Sampaio, Dora (2019)
International retirement migration has been typically regarded as a couple’s project. Much less is known about single lifestyle migrants who settle and age abroad and those who, after the loss of their spouse, decide to stay put. Informed by a larger pool of 36 life-narrative interviews with later-life lifestyle migrants in the Azores, and structured around four selected portrayals, this paper seeks to explore meanings of place in later life and to unpack the complex set of negotiations that the ageing self undergoes in a context of migration. Drawing on relational and unbound understandings of place, I question traditional assumptions that see single older migrants abroad as vulnerable and dependent, emphasising a more complex set of needs, desires and expectations in (and for) later-life. For these migrants, emplaced living and ageing experiences are ambiguously mixed. The islands are described as places of freedom and self-actualisation, and also “safe ports” in later-life. Yet, this does not prevent intermittent feelings of isolation and loneliness, including the desire to restore some sense of companionship and romantic life.